2018
DOI: 10.1037/bne0000263
|View full text |Cite
|
Sign up to set email alerts
|

Rapid effects of sex steroids on zebra finch (Taeniopygia guttata) pair maintenance.

Abstract: Although steroids are widely known to affect behavior through activation of nuclear/cytosolic receptors (“genomic” effects), steroids can also rapidly affect behavior via modulation of signal transduction pathways (“nongenomic,” fast actions, or rapid effects). In zebra finches, there is evidence that sex steroids have context-specific effects on pair-maintenance behavior, on both acute and chronic timescales. Here, we quantified the effects of orally administered testosterone and 17β-estradiol (E2) on pair-ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 60 publications
(136 reference statements)
1
6
0
Order By: Relevance
“…In this way, time-stamped calls were identified for each bird within a dyad. Previous experiments using similar partner separation–reunion paradigms have found that this context primarily elicits stack-like short calls and some distance calls, and very few tet-like short calls or male songs (Gill, Goymann, Ter Maat, & Gahr, 2015; Prior et al, 2018). Although we did not score call types in the current study, the vast majority of vocalizations we heard on the recordings were stack-like calls.…”
Section: Methodsmentioning
confidence: 94%
See 1 more Smart Citation
“…In this way, time-stamped calls were identified for each bird within a dyad. Previous experiments using similar partner separation–reunion paradigms have found that this context primarily elicits stack-like short calls and some distance calls, and very few tet-like short calls or male songs (Gill, Goymann, Ter Maat, & Gahr, 2015; Prior et al, 2018). Although we did not score call types in the current study, the vast majority of vocalizations we heard on the recordings were stack-like calls.…”
Section: Methodsmentioning
confidence: 94%
“…Our behavioral set up is illustrated in Figure 1. This behavioral assay is based on partner separation and reunion paradigms used previously (Prior, Fernandez, Soula, & Vignal, 2018; Prior, Yap, & Soma, 2014). However, in this paradigm, we focus on the finer, moment-to-moment details of behavior.…”
Section: Methodsmentioning
confidence: 99%
“…This focus is particularly relevant for animal behavior research, where the terms behavioral synchrony and coordination are less pervasive than in human research. For example, spatial proximity or coordinated activities, which are commonly used dependent variables ( Prior et al, 2014 , 2016 , 2018 ; Prior and Soma, 2015 ), are not referred to in the literature as measures of synchrony, despite that they would be classified as synchrony by the above definitions. Considered generally, spatial proximity itself is a hallmark of pair bonding and social bonding in birds and other species ( Black and Hulme, 1996 ; Frigerio et al, 2001 ; Emery Thompson, 2019 ; Szipl et al, 2019 ); but such research lines are not included here.…”
Section: A Note On Methods: Behavioral Synchronymentioning
confidence: 99%
“…By this reasoning, it may be assumed that strongly bonded pairs display more affiliative behaviors across domains. However, various disruptions (e.g., brief stressors, pharmacological and hormonal manipulations) often affect one type of affiliative behavior and not another (Prior et al, 2014), or affect different types of behaviors in opposing ways (Prior et al, 2016(Prior et al, , 2018. Such experiments raise the question of how different behavioral components contribute to the formation and maintenance of pair bonds as well as how to assess the consequences of such perturbations on pair bonds.…”
Section: Challenges In Studying Pair Bondingmentioning
confidence: 99%
See 1 more Smart Citation